Tipe dan proporsi saluran pemasaran komoditi ikan Kakap Merah (Lutjanus spp) pada Pelabuhan Perikanan Samudera Kendari - Kurniawan, Muhammad; Mansyur, Akhmad; Nur, Andi Irwan; Sidiq, Azwar (Jurnal Sosial Ekonomi Perikanan, 2025)
This research aims to determine the market share and type of marketing channels, as well as the marketing volume proportion of red snapper (Lutjanus spp) at the Kendari Ocean Fisheries Port. This research was conducted in January-February 2014. The sampling technique used was purposive sampling. Research data was obtained through observation, interviews, documentation and literature study. The types of data used in this research are primary data and secondary data. The data analysis used is descriptive analysis with a nominal and percentage approach. The research results show that at PPS Kendari there are three markets, namely local, domestic and export. The local market has two types of marketing channels, while the domestic and export markets only have one type of marketing channel. The highest proportion of local market marketing volume is in channel type I with a value of 69% and the lowest is in channel type II with a value of 31%. The proportion of red snapper commodity marketing volume is mostly marketed in the local and domestic markets, while the export market has a smaller number of commodity markets. The highest proportion of red snapper marketing volume in the 2016-2020 period was in the local and domestic markets at 38%, while in the export market it was 24%.